Influence of Executive Compensation on Firm Risk-Taking Behavior in Qatar - Kasun, Lola (American Journal of Finance, 2024)
Purpose: The aim of the study was to assess the influence of executive compensation on firm risk-taking behavior in Qatar. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study indicated that the structure and magnitude of executive compensation can significantly impact the risk profile of a firm. When executives are rewarded with substantial stock options and performance-based incentives, they are often motivated to pursue riskier strategies that have the potential for higher returns, aligning their interests with those of shareholders. However, this can also lead to excessive risk-taking, which may jeopardize the firm's stability if not managed properly. Conversely, fixed salaries and lower levels of variable compensation tend to promote more conservative decision-making, reducing the propensity for risk. The balance and design of executive compensation packages are thus crucial in ensuring that executives take calculated risks that contribute to sustainable firm growth rather than engaging in hazardous financial behaviors that could lead to adverse outcomes. Implications to Theory, Practice and Policy: Agency theory, tournament theory and stewardship theory may be used to anchor future studies on assessing the influence of executive compensation on firm risk-taking behavior in Qatar. Implement compensation structures that strategically align executive incentives with organizational risk strategies. Collaborate with regulatory bodies to enhance governance frameworks that govern executive compensation.